Biotech and innovative breeding for the new Agri-Food System CGIAR Research Programs (CRPs) - Ellul, P. (CGIAR System Organization, 2016)
10th Asia-Pacific Biotech Congress, Bangkok Thailand. By P. Ellul, Senior Officer, CGIAR System Organization, 25-27 July 2016